KEANEKARGAMAN FLORA ANGGREK (ORCHIDACEAE) DICAGAR ALAM GUNUNG SIMPANG, JAWA BARAT - Diah Sulistiarini (BERITA BIOLOGI, 2009)
Species diversity of orchids in The Gunung Simpang Nature Reserve. Cianjur. West Java was investigated, where thirty three species of orchids are recorded. Two species (Ceraiosiylis capiialu Z. & M. and Trichogloitis ngida Bl.) are regarded as endemic. Three species are new records to Java namely Appendicula babiensis J.J.Sm., A. aberrans Schltr. and Bulbophyllum appressicaule Ridl.